Targeted rescue of a polycystic kidney disease mutation by lysosomal inhibition - Hofherr, Alexis; Wagner, Claudius; Watnick, Terry; Köttgen, Michael (Kidney international, 2016)
Autosomal dominant polycystic kidney disease (ADPKD) is the most common monogenic cause of end-stage renal disease. The molecular pathogenesis of ADPKD is not completely known, and there is no approved therapy. To date, there is limited knowledge concerning the molecular consequences of specific disease-causing mutations. Here we show that the ADPKD missense variant TRPP2D511V greatly reduces TRPP2 protein stability, and that TRPP2D511V function can be rescued in vivo by small molecules targeting the TRPP2 degradation pathway. Expression of the TRPP2D511V protein was significantly reduced compared to wild-type TRPP2. Inhibition of lysosomal degradation of TRPP2D511V by the US Food and Drug Administration (FDA)-approved drug chloroquine strongly increased TRPP2 protein levels in vitro. The validation of these results in vivo requires appropriate animal models. However, there are currently no mouse models harboring human PKD2 missense mutations, and screening for chemical rescue of patient mutations in rodent models is time-consuming and expensive. Therefore, we developed a Drosophila melanogaster model expressing the ortholog of TRPP2D511V to test chemical rescue of mutant TRPP2 in vivo. Notably, chloroquine was sufficient to improve the phenotype of flies expressing mutant TRPP2. Thus, this proof-of-concept study highlights the potential of directed therapeutic approaches for ADPKD, and provides a rapid-throughput experimental model to screen PKD2 patient mutations and small molecules in vivo.